The Rise of Bullying at the Early Childhood Education Level - Budiyanti, Dewi; Slamet, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This research aims to explore the phenomenon of increasing cases of bullying among young children, identify the causal factors, and analyze the impact on children's social and emotional development. Apart from that, this research also attempts to formulate effective prevention and intervention strategies to overcome the problem of bullying. Methodology: This research uses a qualitative approach which has been carried out, it can be concluded that the phenomenon of bullying in early childhood education is a serious problem that requires immediate attention and treatment from various parties. Several important points that can be taken from this research include: The forms of bullying that occur tend to be verbal and social, such as teasing, isolating and spreading rumors. Results: The results of the study show cases of bullying among young children, in various forms ranging from physical to social exclusion. The main factors contributing to this phenomenon include inappropriate media exposure, lack of adult supervision, and minimal character education at school and home. The impact of bullying on victims includes decreased self-confidence, difficulty socializing, and emotional disturbances. Effective prevention strategies involve a holistic approach to the role of schools, families and communities in building safe environments for children. Applications/Originality/Value: This research provides a new contribution to the understanding of the dynamics of bullying in early childhood by involving various stakeholders. The findings of this, research can be the basis for developing policies and intervention programs that are more targeted in dealing with the problem of bullying in early childhood.